Diet and acne: an exploratory survey study of patient beliefs - Quynh-Giao Nguyen; Ramsey Markus; Rajani Katta (Mattioli1885, 2016)
Background: In the past, medical literature reflected that diet was not a proven cause of acne. However, studies in recent years have substantiated a link between certain dietary factors and acne. It is unclear whether patients are aware of recent research findings. Objectives: Acne patients were surveyed to explore beliefs regarding the link between diet and acne, to determine whether these beliefs translated into behavior change and to identify health information sources. Patients/Methods: Upon Institutional Review Board (IRB) approval, surveys were administered to 50 acne patients at an academic dermatology clinic in 2014, with 49 completed in full and included in this analysis. Results: Ninety-two percent of respondents believed that diet could affect acne. Seventy-one percent attempted to change their diet to improve acne. Seventy-one percent believed acne to be caused by fried or greasy foods, although chocolate (53%), dairy (47%), and soda drinks (35%) were highly implicated. Patients obtained information from Google searches (49%), dermatologists (43%), family members and TV (41% each), and medical websites (31%). Conclusions: In this exploratory study, patients reported utilizing a diversity of information sources, a majority from the Internet. In those surveyed, there was a persistence of long-held belief that fried/greasy foods and chocolate may serve as acne triggers, and less belief in trigger foods supported by recent research, including refined carbohydrates and sugar. Given the multiplicity of beliefs and utilized sources among acne patients in our survey, there is a need to establish up-to-date and reliable methods to educate patients on diet and acne.